Assessing interest in STEM career survey among Malaysian form four science stream student - Razali, Fazilah; Talib, Othman; Abdul Manaf, Umi Kalthom; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This study is a presentation of the construction, validity and reliability of the instruments chosen to measure STEM related career interest, among Form Four students. This study consists of 4 sub-sections measuring the following dimensions: STEM- related career interest, attitudes towards science, motivation and parental influence. The construction process includes the reevaluation of each construct for every instrument chosen, adaptation of it into Bahasa Melayu, the modification of every statement in the instrument to suit the scope of study, as well as the learning environment of students in Malaysia, and the validation by the panel of experts. The construction of this instrument is based on two theories, which are Eisner’s Curriculum Theory (1979), which emphasizes students’ needs in the curriculum, and Social Career Cognitive theories (SCCT) (2013), based on the suitability of the current learning environment and future learning needs. The analysis of the reliability of each construct proves that the instrument is able to measure students’ STEM-related career interest. The implication of the instrument for future use, is also discussed.